Method for manufacturing micro-optical glass elements
By controlling silica content and pH levels, and using a silica gel mold with reduced sintering temperatures, the method addresses the high-cost and complex issues of fine optical glass element production, achieving efficient and cost-effective mass production of transparent micro-structured glass elements.
Patent Information
- Application Number
- JP2022502226
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-31
- Filing Date
- 2020-12-10
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-12-10
AI Technical Summary
Existing methods for manufacturing fine optical glass elements are costly, complex, and unsuitable for mass production due to high equipment costs, processing difficulties, and material inefficiencies, particularly in creating micro-structured glass elements.
A method involving the use of a silica dispersion with controlled silica solid content and molar ratios, adjusted pH levels, and reduced sintering temperatures to produce fine optical glass elements, utilizing a silica gel mold for shaping and sintering at 1100 °C or less.
This approach reduces production costs and simplifies the process, enabling high-yield production of transparent, micro-structured glass elements with reduced shrinkage and surface defects, suitable for mass production.
Smart Images

Figure 0007624964000002 
Figure 0007624964000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of glass manufacturing, and in particular to a method for manufacturing micro-optical glass elements. [Background technology]
[0002] In recent years, with the rapid development of optical design technology in the projection field, large and bulky projectors are being replaced by portable projectors with sophisticated structures and small size, and projection technology is also moving further to smart terminals, such as mobile phones and smart glasses. Accordingly, the demand for fine shaping and modulation of light beams is increasing due to the reduction in the volume of optical engines and the reduction in the light spot size. In addition, with the popularization of high-brightness laser light sources, optical elements are required to withstand increasing heat energy when meeting the above-mentioned conditions for fine shaping and modulation of light, and therefore higher heat resistance is also required. Resin-based optical elements can no longer meet the requirements of current optical engine design, and glass optical elements have already become an essential option.
[0003] When manufacturing a micro-optical element (e.g., a microlens array), the method of processing a microstructure on the entire surface of glass (e.g., wrapping) requires high equipment costs, is difficult to process, and is disadvantageous for mass production, while the sol-gel method is a relatively economical manufacturing method. The conventional sol-gel method with high solid content and low shrinkage is suitable for manufacturing large-sized glass elements, but is affected by the processing dimensions of the mold and cannot directly manufacture micro-order micro-optical structures. In contrast, Patent Document 1 proposes a method of manufacturing a micro-glass structure by multiple transfers, in which a large-sized aluminum alloy mold is precisely processed by a high-precision diamond lathe, and an inverse symmetric structure is replicated by stamping silicone rubber, sol is injected into this silicone rubber mold to form it, and the sintered molded glass product (which shrinks in volume at a certain multiple with respect to the aluminum alloy mold) is further used as a mold, silicone rubber is stamped to form a silicone rubber mold with an inverse symmetric structure, and the following multiple transfers are performed in the same manner to realize a micron-order micro-glass structure. However, consumer microprojection systems, which are sold at low margins, are unable to withstand the excessive material and time costs of the above technical solutions, so a more economical method for manufacturing micro-optical glass elements is urgently needed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] CN1761626A Summary of the Invention [Means for solving the problem]
[0005] In response to the drawbacks of the above-mentioned prior art, such as high cost and complicated process, the present invention provides a method for producing a micro-optical glass element with low cost and simple process, which includes the steps of: obtaining a silica dispersion, adding an acidic solution to the silica dispersion so as to adjust the pH value of the silica dispersion, and stirring the mixture; adding tetraethoxysilane to the silica dispersion and stirring the mixture to obtain a sol, adding an alkaline solution to the sol so as to adjust the pH value of the sol, stirring and leaving the mixture to stand; injecting the left sol into a mold and aging it to obtain a wet gel; releasing the wet gel, washing and drying it to obtain a dry gel; and sintering the dry gel to obtain a micro-optical glass element, in which the solid content of silica in the raw material is 25.5% or less.
[0006] In one embodiment, the silica solids content in the feedstock is less than or equal to 25%.
[0007] In one embodiment, the solids content of silica in the feedstock is less than or equal to 20.3%.
[0008] In one embodiment, step 1 includes obtaining a stock silica dispersion having a predetermined molar volume, and mixing the stock silica dispersion with deionized water to adjust the solid content of the silica to obtain the silica dispersion.
[0009] In one embodiment, in the raw material, the molar ratio of silica contained in the silica dispersion to the tetraethoxysilane is 2.8 to 4.7.
[0010] In one embodiment, the molar ratio of silica contained in the silica dispersion to the tetraethoxysilane is 3.8 to 4.7.
[0011] In one embodiment, in the step 1, the acidic solution is a hydrochloric acid solution, and the silica dispersion has a pH value of 1.3 to 2.8 after pH adjustment.
[0012] In one embodiment, in the step 2, the alkaline solution is an aqueous ammonia solution, and the sol has a pH value of 2.5 to 5 after pH adjustment.
[0013] In one embodiment, the mold is a silica gel mold.
[0014] In one embodiment, in step 5, the sintering temperature is 1100° C. or less. Effect of the Invention
[0015] Compared with the prior art, the present invention has the following beneficial effects: by using raw materials with low silica solid content to manufacture micro-optical glass elements by sol-gel method, glass manufacturing with large shrinkage is achieved, glass elements with surface micro-optical structures can be manufactured only once, and multiple transfers with low shrinkage are avoided, which greatly reduces the cost and simplifies the process. [Brief description of the drawings]
[0016] [Figure 1] 1 is a flow chart illustrating a method for producing a micro-optical glass element according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings and embodiments.
[0018] The main idea of the present invention is to control the raw materials of the glass element produced by the sol-gel method, and by combining two kinds of silica sources and simultaneously controlling the solid content of silica, the solid content of the raw materials is low, and the shrinkage rate of the sol-gel method production is large, which breaks through the limitations of the traditional sol-gel method at high solid content. Furthermore, by controlling the ratio of the two kinds of silica sources, the yield problem in the production at low solid content is solved.
[0019] The solid content described in the present invention means the proportion (wt %) of silica (including silica obtained by hydrolysis of tetraethoxysilane) in the raw material to the total raw material.
[0020] 1, which is a flow chart showing the method for producing a micro-optical glass element according to the present invention, includes step 1 of obtaining a silica dispersion and adjusting the pH value, step 2 of producing a sol, step 3 of producing a wet gel, step 4 of producing a dry gel, and step 5 of sintering to obtain a micro-optical glass element. Each step will be described in detail below.
[0021] <Step 1> This step includes obtaining a silica dispersion, adding an acidic solution to the silica dispersion so as to adjust the pH value of the silica dispersion, stirring, and finally obtaining a silica dispersion with a preset pH value as a first silica source.
[0022] In the present invention, the initial silica dispersion (i.e., without adjusting the pH value) is obtained by mixing and stirring the fumed silica with deionized water, and dispersing the fumed silica uniformly in the water by a magnetic stirrer, a homogenizer and / or ultrasonic dispersion, and then filtering the silica dispersion to remove impurities and undispersed agglomerated particles.
[0023] The fumed silica in the present invention has a particle size D50 within the range of 20 nm to 150 nm, and has a large specific surface area.
[0024] Usually, in order to ensure the uniformity of silica dispersion, the above-mentioned process requires a long time, and each production takes a long time.Therefore, in one embodiment of the present invention, a large amount of silica dispersion stock solution with a preset molar volume is pre-arranged, and a certain amount of silica dispersion stock solution is obtained each time production is performed, and mixed and diluted with deionized water to adjust the silica solid content to obtain the silica dispersion of the production batch.Therefore, the adjustment to the silica solid content is simplified, the time required for uniform mixing is shortened, and it is not necessary to filter to remove impurities each time production is performed, which improves production efficiency and improves the stability of raw materials in the production of different batches.
[0025] By adding an acidic solution, which may be, for example, a dilute hydrochloric acid solution, to the silica dispersion and stirring uniformly, the silica dispersion has a pH value of 1.3-2.8 after adjustment. As can be understood, the acidic solution may be other acidic solutions for adjusting the pH value.
[0026] <Step 2> After obtaining an acidic silica dispersion, add tetraethoxysilane to the silica dispersion, stir, hydrolyze tetraethoxysilane, obtain a sol, add an alkaline solution to the sol so as to adjust the pH value of the sol, stir and leave to stand. During the standing process, the sol gradually begins to form a gel, and it is not preferable for this process to be too long, so it is sufficient to leave it to stand for a short time to expel air bubbles generated during the stirring process.
[0027] In an embodiment of the present invention, the alkaline solution may be an aqueous ammonia solution, and the sol has an increased pH value after pH value adjustment, which is finally 2.5 to 5. As can be understood, the alkaline solution may be other alkaline solutions for adjusting the pH value.
[0028] <Step 3> The sol that has been left to stand is poured into a mold and aged to obtain a wet gel.
[0029] In this step, the mold can be of various shapes and sizes as required, so as to obtain glass optical elements of various shapes and sizes. After maturation, the wet gel has a certain strength and can be released from the mold. In order to facilitate the release, the present invention preferably adopts a silica gel mold, and the wet gel can be peeled off within a certain distortion range of the silica gel mold. If a rigid mold is adopted, the fine optical surface structure may be damaged, causing burrs and cracks, while it is difficult to remove the wet gel.
[0030] <Step 4> The wet gel is released from the mold, washed and dried to obtain a dry gel.
[0031] After demolding, a wet gel mass with transferred microstructure is obtained, and certain non-uniform impurities that may exist in the wet gel mass can be washed to remove surface impurities, which helps to obtain a product with higher transparency.
[0032] When drying the wet gel mass, it is not advisable to use a temperature that is too high, otherwise dehydration may occur too rapidly and the sample may crack.
[0033] After drying, a dry gel mass is obtained which has a reduced volume compared to the wet gel mass, and this step is the key to the volume shrinkage in the process of manufacturing micro-optical glass elements.
[0034] <Step 5> The dry gel is sintered to obtain microscopic optical glass elements. In this step, the sample shrinks in volume for a second time, turning from an opaque to a transparent glass element.
[0035] Usually, in the technical solution of manufacturing optical glass by the sol-gel method in the conventional technology, sintering needs to be performed at 1200°C or more, and the inventor found that sintering at high temperatures will damage the edges and surfaces of the optical glass elements, causing the optical glass elements to be slightly distorted and even cracked. In large-sized conventional glass optical elements (e.g., optical elements on the order of millimeters), the impact of such surface defects is not significant, but in fine optical glass elements, it will adversely affect the optical performance of the elements. In the present invention, the inventor found that by reducing the solid content of silica in the raw material, optical elements with high transparency can be obtained even if the sintering temperature is lowered. In a preferred embodiment of the present invention, the sintering temperature is 1100°C or less, which not only protects the micro-optical structure on the glass surface from cracking, but also reduces the risk of crystallization inside due to a low solid content, which reduces the transparency, and improves the product yield. In addition, the reduction in sintering temperature can also reduce energy consumption and manufacturing costs.
[0036] The above describes the preparation steps in detail. In the following, in order to facilitate the comparison of the effects of each technical solution, different solid contents and silica source ratios are selected under the same experimental conditions for comparison with specific examples.
[0037] Working Example First, fumed silica particles and deionized water were weighed, mixed and stirred, and uniformly dispersed using a homogenizer. Dilute hydrochloric acid was added to adjust the pH to 2. After stirring, tetraethoxysilane was added and stirred to form a sol solution. Next, ammonia water was added to adjust the sol to pH = 4. After stirring, the mixture was allowed to stand and then poured into a microstructured mold. It had already gelled after 10 hours and was demolded after 48 hours.
[0038] The wet gel with the above-mentioned microstructure was placed in pure water (deionized water) and circulated for cleaning. After rinsing with water, it was placed in a constant temperature and humidity box at 45°C to dry. After drying, the sample was kept at 1050°C for 12 hours and sintered to obtain an optical element with a microstructure.
[0039] The table below shows a data table of each embodiment and comparative example, where the meaning of solid content refers to the above explanation, the ratio refers to the ratio of the amount of silica (SiO2) material contained in the fumed silica particles or the original silica dispersion liquid to the amount of tetraethoxysilane (TEOS) material, the shrinkage rate refers to the volume shrinkage rate of the sintered glass element relative to the gel after demolding, which can be measured by Archimedes' method, and the yield rate refers to defective products when there are cracks, scratches, stains, air bubbles, and extremely low transmittance.
[0040] [Table 1]
[0041] As can be seen from the above list data, the solid content has a large effect on the shrinkage rate, and in order to obtain optical glass elements of the finest possible size, it is necessary to reduce the solid silica content in the raw material. In the present invention, the solid silica content in the raw material is 25.5% or less. Preferably, the solid silica content in the raw material is 25% or less. More preferably, the solid silica content in the raw material is 20.3% or less so that the shrinkage rate can reach 89% or more.
[0042] The inventors have found that in the present invention, the ratio of two different silica sources greatly affects the product yield and production time. SiO2 / n TEOS When the ratio of the solid content is 3.8, the solid content does not significantly affect the product yield (both are about 60%), and only the shrinkage rate has a clear effect. Therefore, the determination of the ratio of the two silica sources has important significance for the actual mass production of the product.
[0043] Tetraethoxysilane (TEOS) contributes to the gelation process. If the silica dispersion is used as the only silica source, the gel formation process is extremely slow, making it impossible to mass-produce the product. As the amount of tetraethoxysilane is increased, the required gelation time gradually decreases. According to the inventor's research, the molar ratio n of silica to tetraethoxysilane contained in the silica dispersionSiO2 / n TEOS is 4.7 or less, the requirements for mass production can be met.
[0044] However, if there is too much tetraethoxysilane, the gel may crack upon shrinkage. SiO2 / n TEOS The smaller the n, the lower the yield. SiO2 / n TEOS As the ratio drops to 2.8, the yield drops to 40%, and smaller ratios are not of significant economic value.
[0045] The present invention does not require that only a method with a 100% yield be adopted, but rather that yield and production time must be considered comprehensively. A high yield always means a longer gelation time, and it is sufficient to have a larger number of non-defective products per unit time.
[0046] Therefore, in the present invention, the molar ratio of silica to tetraethoxysilane contained in the silica dispersion is 2.8 to 4.7. Preferably, the molar ratio of silica to tetraethoxysilane contained in the silica dispersion is 3.8 to 4.7 so that a yield of 60% or more is guaranteed.
[0047] In the present specification, the embodiments will be described in a step-by-step manner, with a focus on the differences between each embodiment and other embodiments, and reference may be made to the same or similar parts between the embodiments.
[0048] The above description is merely an embodiment of the present invention, and does not limit the patent scope of the present invention. Any modification of the equivalent structure or equivalent flow described in the specification and drawings of the present invention, or any direct or indirect application to other related technical fields, is similarly included in the patent protection scope of the present invention.
Claims
1. A method for producing a micro-optical glass element, comprising the steps of: Step 1: obtaining a silica dispersion, adding an acidic solution to the silica dispersion so as to adjust the pH value of the silica dispersion, and stirring the obtained solution; Step 2: adding tetraethoxysilane to the silica dispersion and stirring to obtain a sol; adding an alkaline solution to the sol so as to adjust the pH value of the sol; stirring and allowing to stand; Step 3: pouring the sol that has been left to stand into a mold and aging it to obtain a wet gel; Step 4: releasing the wet gel, washing and drying it to obtain a dry gel; and step 5 of sintering the dry gel to obtain micro-optical glass elements. A method for producing a fine optical glass element, characterized in that the solid content of silica in the raw material is 20.3% to 25.5%.
2. 2. The method for producing a micro-optical glass element according to claim 1, wherein the step 1 includes obtaining a stock solution of silica dispersion having a predetermined molar volume, mixing the stock solution of silica dispersion with deionized water to adjust the solid content of the silica, and obtaining the silica dispersion.
3. 3. The method for producing a micro-optical glass element according to claim 1, wherein in the raw material, a molar ratio of silica contained in the silica dispersion to the tetraethoxysilane is 2.8 to 4.
7.
4. 4. The method for producing a micro optical glass element according to claim 1, wherein a molar ratio of silica contained in the silica dispersion to the tetraethoxysilane is 3.8 to 4.
7.
5. The method for producing a micro-optical glass element according to any one of claims 1 to 4, characterized in that in step 1, the acidic solution is a hydrochloric acid solution, and the silica dispersion has a pH value of 1.3 to 2.8 after pH adjustment.
6. 6. The method for producing a micro-optical glass element according to claim 1, wherein in step 2, the alkaline solution is an aqueous ammonia solution, and the sol has a pH value of 2.5 to 5 after pH adjustment.
7. 7. The method for producing a micro-optical glass element according to claim 1, wherein the mold is a silica gel mold.
8. 8. The method for producing a micro optical glass element according to claim 1, wherein in step 5, the sintering temperature is 1100° C. or less.
Citation Information
Patent Citations
Optical articles and sol-gel process for their manufacture
CN1761626A
Production of silica glass
JP1987292642A
Production of distributed index lens
JP1991137027A
Method for producing glassy monolith via sol-gel process
JP2009137836A
Sol-gel method
JP2010502554A